Analisis interpretasi lirik dabus yang diamalkan oleh masyarakat di Bagan Serai Perak - Rosly, Nurfarhana Shahira; Yusop, Mohd Sharifudin (Penerbit Universiti Malaysia Terengganu, 2014)
Dabus is a game that show the immunity to try to injure themselves. The objective of this study is to analyze aspects of the message in the Dabus performances song with the community at Bagan Serai Perak. This study was conducted to analyze aspects of the message that contained in the songs that were performed during the course of this Dabus Dance implemented. Young Dabus players and dancers at Bagan Serai Perak act as informants in this study. Informants were selected based on the participation in Dabus performances, as an appreciation of their culture in depth about the message that were contained in the song. The study’s method was a combination of interview, recording, observation and writing the manuscript. Informants were interviewed by means of open-ended questions about the meaning of a song and implicit messages that contained in the song. The data that received at the end of study was analyzed by linking with Social Theory of Literature. Sociological literature came from the sociology and literature which is the orientation approach by the author. The results show the existence of the message in the lyrics that dismantling of human relationships with God, society and culture, natural beauty, heroism, education and cultural acculturation. This study is expected to infuse back magnificence of Malay art. The study of these Malay art should be enhanced to lift back the glory of the Malay race.